Emotional intelligence in leadership styles of human resources managers in Peruvian retail companies - Armesto-Céspedes, Miguel Sebastián (2024)
n the post-pandemic era, organizational challenges have intensified, particularly in leadership and management within the retail sector. This study focuses on the pivotal role of Emotional Intelligence (EI) in shaping leadership styles among human resource managers. Given the complexities introduced by the pandemic, which include managing remote teams and addressing heightened emotional stressors, the study argues that leaders must possess a profound understanding of both their own and their team members’ emotional dynamics. Employing a quantitative approach, the study surveyed 385 human resource managers across Peruvian retail companies to assess how EI influences their leadership styles. The analysis utilized ordinal logistic regression, revealing that EI significantly affects leadership modalities, accounting for 27,2 % of the variation in leadership styles. This suggests that EI is a critical predictor of effective leadership. The findings underscore the necessity for HR leaders to excel in emotional management, which is essential not only for improving team cohesion and workplace atmosphere but also for enhancing overall business profitability. The study concludes that in the evolving retail landscape, fostering leaders with high EI could be the key to navigating post-pandemic challenges effectively.